Post–Liver Transplant Leptin Results in Resolution of Severe Recurrence of Lipodystrophy‐Associated Nonalcoholic Steatohepatitis. Issue 11 (5th September 2013) - Casey, S. P.; Lokan, J.; Testro, A.; Farquharson, S.; Connelly, A.; Proietto, J.; Angus, P. W.
Abstract: We describe the first case of a patient undergoing orthoptic liver transplantation for acquired generalized lipodystrophy‐related nonalcoholic steatohepatitis who developed severe recurrence of nonalcoholic fatty liver disease in the first few months posttransplant but responded rapidly to the administration of exogenous leptin. The beneficial effects of therapy were supported by histology along with magnetic resonance spectroscopy studies, which demonstrated that leptin therapy greatly reduced fat deposition in the liver. Leptin therapy may have a role to play in preventing patients with lipodystrophy developing end‐stage liver disease or in rescuing such patients who develop disease recurrence postliver transplantation. Abstract : This case report describes the use of leptin therapy to reverse nonalcoholic steatohepatitis recurrence in a patient with acquired generalized lipodystrophy and associated nonalcoholic fatty liver disease who underwent liver transplantation.